Equality before the Law Principle and the Legal Aid for the Poor: An Indonesian Insight - Lutfiyah, Khoirum (The Indonesian Journal of International Clinical Legal Education, 2021)
Legal aid is something that is given by the state to people who are unable to get justice and their basic rights before the law. The state has an obligation to protect every citizen, especially legal protection for the poor or the poor. To ensure this protection, the government forms a law which can help the underprivileged or poor in dealing with the legal problems they experience. With the existence of the Law on Advocacy, the Law on Legal Aid, as well as the existence of this Legal Aid Institute, it is hoped that it will be able to reduce the burden on what people experience before the law, especially related to the costs of legal aid.